2022
DOI: 10.3389/fped.2022.834363
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers' Intention to Vaccinate Their Children Under 12 Years of Age Against COVID-19: A Cross-Sectional Multi-Center Study in Milan, Italy

Abstract: The impact of Coronavirus disease 2019 (COVID-19) on the pediatric population is increasingly recognized. A widespread vaccination in childhood would provide benefits for children and might help ending the pandemic by enhancing community protection. Following recent approval by the European Medicines Agency (EMA) of Comirnaty (Pfizer-BioNTech) for children aged 5–11 years, we aimed to investigate caregivers' intention to vaccinate their children <12 years of age against COVID-19. A structured questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Another significant aspect is the distrust or doubts about vaccination against COVID-19 and its efficacy [ 20 , 21 , 24 , 27 , 34 , 38 , 44 , 49 , 51 , 52 , 53 ]. As easily expected, the attitude of refusal towards vaccinations or the adoption of poorly protective behaviours constitutes a further preponderant element predisposing to VH against COVID-19 [ 24 , 26 , 27 , 28 , 30 , 37 , 39 , 40 , 42 , 48 , 51 ]. Another predisposing element is the lack of awareness of contracting the infection [ 18 , 31 , 33 , 34 , 37 , 42 , 44 , 46 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another significant aspect is the distrust or doubts about vaccination against COVID-19 and its efficacy [ 20 , 21 , 24 , 27 , 34 , 38 , 44 , 49 , 51 , 52 , 53 ]. As easily expected, the attitude of refusal towards vaccinations or the adoption of poorly protective behaviours constitutes a further preponderant element predisposing to VH against COVID-19 [ 24 , 26 , 27 , 28 , 30 , 37 , 39 , 40 , 42 , 48 , 51 ]. Another predisposing element is the lack of awareness of contracting the infection [ 18 , 31 , 33 , 34 , 37 , 42 , 44 , 46 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another predisposing element is the lack of awareness of contracting the infection [ 18 , 31 , 33 , 34 , 37 , 42 , 44 , 46 , 49 ]. Furthermore, four studies found that knowing people who have contracted the COVID-19 disease affects the decision to undergo the vaccination [ 26 , 30 , 33 , 42 ]. Finally, the preference for natural immunity or having contracted COVID-19 before vaccination are both conditioning factors for the decision to undergo the vaccine [ 24 , 35 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In global surveys, the caregivers' attitude towards paediatric COVID-19 vaccination ranged from low hesitancy (2.8%) in Brazil to a higher hesitancy of 23-44% in Italy. [32][33][34] Introducing new vaccines for the paediatric population is quite challenging and, at the same time, pivotal as paediatric and adolescent immunization is essential TherapeuTic advances in vaccines and immunotherapy for achieving a substantial degree of community protection and herd immunity. Primary healthcare providers and family physicians need to be offered technical and scientific training so that they can address the concerns rationally and scientifically.…”
Section: Therapeutic Advances In Vaccines and Immunotherapymentioning
confidence: 99%
“…Considering the age variable, despite the greater adherence to the campaign by the over-60-year-old population (60.3%) [ 58 ], approximately 18.3% of the doses were administered in the 2–6-year-old population. The focus on vaccination in this population, attention on the part of parents or caregivers, has in fact been widely analyzed in the literature [ 29 , 59 , 60 , 61 ]. For this reason and in order to achieve greater compliance on the part of the pediatric patient as well as for their greater efficacy [ 62 , 63 ], trans nasal spray vaccines have been used in this population [ 61 ].…”
Section: Discussionmentioning
confidence: 99%